The Influence of Human Resource Management Practices on Employee Productivity at PT. Unggul Widya Teknologi Lestari (PT. UWTL) Pasangkayu - Aprilia Amalia Widyastuti; Jati Waskito (Indonesian Interdisciplinary Journal of Sharia Economics)
Employee productivity is one of the indicators of a company's success. Employee productivity will show the extent to which employees can complete tasks efficiently and effectively to achieve company goals. Employee productivity in a company can be influenced by compensation, training, and employee performance appraisal. This study was conducted to test and analyze the effect of HR practices of compensation, training, and employee performance appraisal activities on employee productivity at PT. Unggul Widya Teknologi Lestari (PT. UWTL) Pasangkayu. The sample used in this study was 130 people, with a survey method. Data collection was carried out by distributing questionnaires. The analysis technique used was multiple linear regression analysis. The results of the study showed that compensation, training, and employee performance appraisal had a positive and significant effect on employee productivity at PT. Unggul Widya Teknologi Lestari (PT. UWTL) Pasangkayu.